Contra el mito de la neutralidad de la ciencia : el papel de la Historia - Catalan Fernàndez, Albert; Catany Escandell, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Most of the teachers of Science lack theoretical explicit elements to guide their educational action. So they contribute to transmit the myth of neutrality in the scientific orientation and development, and, in this case, Science can fulfil a ruling and justifying role. Against this proposal, we suggest a conscious assumption of some values in the general context of scientific education and even in the general one of a rational education. We put special emphasis on Science as a basic and necessary reference to individual and social behaviour, but not an exclusive one. We also propose: 1) recovering the utopic sense of Modern Science that took place in its origins, and 2) investigating the environment, its past, present and future as a guide to place the student in a nonalienated from and self-forgetful connexion. And, finally, we declare for reason and against oppresion.